Penguatan Karakter Siswa Dalam Kegiatan Pembelajaran Geometri Berbasis Etnomatematika Terhadap Batik Pandeglang Berkah - Ida Ida; Achmad Hufad; Suroso Mukti Leksono (Peneliti.net, 2022)
Mathematics as a branch of science that cannot be separated from human life. Without realizing it, human activities do not escape the use of mathematical concepts in it, one of which is culture that often contains elements of mathematics. Ethnomathematics is a mathematical concept embodied in culture. Ethnomathematics is the link between culture, mathematics and education. This study aims to examine Pandeglang Batik which is associated with the cultivation of student character. This research was conducted with descriptive qualitative method to describe the mathematical values and characters contained in Batik Pandeglang. From the research results obtained mathematical concepts in the form of flat shapes, translations, reflections, dilations and rotations on the Pandeglang batik motif. Through this learning can shape the character of students in accordance with the personality of the Indonesian nation